Disaster rules - Russell, Rob. (Chichester, West Sussex : Wiley-Blackwell, 2011)
Here are 100 disaster management rules to reflect on, remember and follow in the immediate aftermath of an incident involving mass casualties. Each rule is a single-page long, providing the essential information to inform the most common critical decisions you will have to make in either a civilian or military environment. Written by clinicians with deep clinical and operational experience, these rules are concise evidence-based guidelines for all medical personnel dealing with disasters at the scene or in hospital. Based on the Major Incident Medical Management and Support system widely adopt.
Golden rules -- Command and control rules -- Safety rules -- Communication rules -- Assessment rules -- Triage rules -- Treatment rules -- Transport rules -- Hospital rules -- Mass gatherings -- Special incidents -- The last rule.
Includes bibliographical references and index.
Print version record.
Keywords: Disaster medicine -- Rules; Emergency management -- Rules; Medicine; SOCIAL SCIENCE -- Disasters & Disaster Relief; Disaster medicine; Emergency management; Electronic books; Disaster Planning; Emergency Medical Services; Mass Casualty Incidents; Electronic books; Rules; Electronic books